Renal cell carcinoma with a tumor thrombus extending into the right ventricle a case report - Takenaka, A (Hinyokika kiyo. Acta urologica Japonica, 1994)
A case of left renal cell carcinoma extending into the right ventricle was reported. The 72-year-old male entered Kansai Rosai Hospital because of dyspnea. Cardiac and abdominal ultrasonography revealed a left renal tumor with a tumor thrombus extending into the right ventricle. Left nephrectomy and removal of the intracaval and intracardiac tumor thrombus were performed with cardiopulmonary bypass. We also analyzed and discussed the 17 cases, including our case, reported in Japan